Deoxycholic acid promotes development of gastroesophageal reflux disease and Barrett's oesophagus by modulating integrin‐αv trafficking. Issue 12 (22nd September 2017) - Prichard, David O.; Byrne, Anne Marie; Murphy, James O.; Reynolds, John V.; O'Sullivan, Jacintha; Feighery, Ronan; Doyle, Brendan; Eldin, Osama Sharaf; Finn, Stephen P.; Maguire, Aoife; Duff, Deirdre; Kelleher, Dermot P.; et al.
Abstract: The fundamental mechanisms underlying erosive oesophagitis and subsequent development of Barrett's oesophagus (BO) are poorly understood. Here, we investigated the contribution of specific components of the gastric refluxate on adhesion molecules involved in epithelial barrier maintenance. Cell line models of squamous epithelium (HET‐1A) and BO (QH) were used to examine the effects of bile acids on cell adhesion to extracellular matrix proteins (Collagen, laminin, vitronectin, fibronectin) and expression of integrin ligands (α3, α4, α5, α6 and αν ). Experimental findings were validated in human explant oesophageal biopsies, a rat model of gastroesophageal reflux disease (GORD) and in patient tissue microarrays. The bile acid deoxycholic acid (DCA) specifically reduced adhesion of HET‐1A cells to vitronectin and reduced cell‐surface expression of integrin‐αν via effects on endocytic recycling processes. Increased expression of integrin‐αv was observed in ulcerated tissue in a rat model of GORD and in oesophagitis and Barrett's intestinal metaplasia patient tissue compared to normal squamous epithelium. Increased expression of integrin‐αν was observed in QH BO cells compared to HET‐1A cells. QH cells were resistant to DCA‐mediated loss of adhesion and reduction in cell‐surface expression of integrin‐αν . We demonstrated that a specific component of the gastric refluxate, DCA, affects the epithelial barrier through modulation of integrin αν expression, providing a novel mechanism for bile acid‐mediated erosion of oesophageal squamous epithelium and promotion of BO. Strategies aimed at preventing bile acid‐mediated erosion should be considered in the clinical management of patients with GORD.